The earth, the city, and the hidden narrative of race / Carl Anthony. - Anthony, Carl
"Carl Anthony's memoir interweaves urban history, racial justice, and cosmology with personal experiences as an architect/planner, environmentalist, and Black American. By connecting struggles for social and racial justice to the Universe Story, it creates new story for our time"--